The Role of Molecular Biomarkers in the Diagnosis and Prognosis of Brain Infections - Salsabila, Adilah Nur; Ramdhini, Tisya Nasywa; Pramudiantara, Gede Naradhea (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Brain infections are among the most severe neurological disorders, with high morbidity and mortality. Conventional diagnostic approaches often face limitations in sensitivity, specificity, and time efficiency. Advances in molecular biotechnology have introduced molecular biomarkers as valuable tools for improving diagnostic and prognostic precision. This literature review, based on publications from 2015 to 2024 retrieved from PubMed, ScienceDirect, ProQuest, SpringerLink, and Google Scholar, aims to explore the role of molecular biomarkers in brain infections. Pathogen based biomarkers such as Polymerase Chain Reaction (PCR), Loop Mediated Isothermal Amplification (LAMP), and multiplex assays enable rapid and specific pathogen detection, while host response biomarkers, including cytokines such as IFN-γ, TNF-α, and IP-10, as well as ferritin and lactate levels in cerebrospinal fluid, reflect neuroinflammatory processes. The integration of pathogen detection and host response biomarkers enhances diagnostic accuracy, facilitates individualized therapeutic strategies, and contributes to improved clinical outcomes in neuroinfectious diseases.